Exploring the Motive of Muslim Consumers’ Intention Toward Goat’s Milk Purchasing in Malaysia: A Focus Group Interview - Aimi Fadzirul Kamarubahrin; Asmaddy Haris; Jamal Abdul Nassir Shaari; Syadiyah Abdul Shukor (IAIN Salatiga, 2019)
Abstract This study aims to conceptualize the motive of Muslim consumers’ intention toward goat’s milk purchasing in Malaysia. Two focus group discussion sessions involving 10 existing Muslim consumers’ who are purchased goat’s milk were conducted. Preliminary findings from this qualitative study showed that health and price played a significant role in Muslim consumers’ intention toward purchasing goat’s milk. Other three motives of Muslim consumers’ intention toward purchasing goat’s milk is taste, religiosity and nutritious. Recommendation for future studies is provided at the end of the paper.Abstrak Kajian ini bertujuan untuk mengenal pasti motif niat pengguna Islam terhadap pembelian susu kambing di Malaysia. Kajian lepas yang berkaitan telah dibincangkan dan dua sesi perbincangan kumpulan berfokus melibatkan 10 orang pengguna Islam yang membeli susu kambing telah dijalankan. Penemuan awal dari kajian kualitatif ini menunjukkan bahawa faktor kesihatan dan harga memainkan peranan penting dalam niat pengguna Islam untuk membeli susu kambing. Tiga lagi motif niat pengguna Islam terhadap pembelian susu kambing adalah rasa, agama dan khasiat. Cadangan untuk kajian masa depan disediakan pada bahagian akhir artikel.